The dose-response effects of flurbiprofen, indomethacin, ibuprofen, and naproxen on primary skeletal muscle cells - Brandon M. Roberts; Alyssa V. Geddis; Ronald W. Matheny (Taylor & Francis Group, 2024)
ABSTRACTBackground Non-steroidal anti-inflammatory drugs (NSAIDs) like ibuprofen, flurbiprofen, naproxen sodium, and indomethacin are commonly employed for their pain-relieving and inflammation-reducing qualities. NSAIDs work by blocking COX-1 and/or COX-2, enzymes which play roles in inflammation, fever, and pain. The main difference among NSAIDs lies in their affinity to these enzymes, which in turn, influences prostaglandin secretion, and skeletal muscle growth and regeneration. The current study investigated the effects of NSAIDs on human skeletal muscle cells, focusing on myoblast proliferation, differentiation, and muscle protein synthesis signaling.Methods Using human primary muscle cells, we examined the dose-response impact of flurbiprofen (25-200 µM), indomethacin (25-200 µM), ibuprofen (25-200 µM), and naproxen sodium (25-200 µM), on myoblast viability, myotube area, fusion, and prostaglandin production.Results We found that supraphysiological concentrations of indomethacin inhibited myoblast proliferation (−74 ± 2% with 200 µM; −53 ± 3% with 100 µM; both p < 0.05) compared to control cells and impaired protein synthesis signaling pathways in myotubes, but only attenuated myotube fusion at the highest concentrations (−18 ± 2% with 200 µM, p < 0.05) compared to control myotubes. On the other hand, ibuprofen had no such effects. Naproxen sodium only increased cell proliferation at low concentrations (+36 ± 2% with 25 µM, p < 0.05), and flurbiprofen exhibited divergent impacts depending on the concentration whereby low concentrations improved cell proliferation (+17 ± 1% with 25 µM, p < 0.05) but high concentrations inhibited cell proliferation (−32 ± 1% with 200 µM, p < 0.05).Conclusion Our findings suggest that indomethacin, at high concentrations, may detrimentally affect myoblast proliferation and differentiation via an AKT-dependent mechanism, and thus provide new understanding of NSAIDs' effects on skeletal muscle cell development.